Sexual surveillance and control in a community based intellectual disability service - Feely, Michael (My University, 2016)
Within contemporary policy documents regarding intellectual disability and sexuality we often find a progress narrative that contrasts a dark past, when the sexuality of disabled people was suppressed, with an enlightened present, when we recognize the sexual rights of all human beings. In this paper – which pertains to the Republic of Ireland – I take up the Foucauldian and Deleuzian position of treating such progress narratives with suspicion. From this perspective, I offer an alternative reading of the treatment of intellectual disability and sexuality in the present, and I seek to map just some of the subtle but effective ways this population’s sexuality continues to be controlled today
PUBLISHED
Keywords: Assemblage; Deleuze; Foucault; intellectual disability; sexuality; surveillance; Identities in Transformation; Inclusive Society; DISABILITY; Disability Studies; INTELLECTUAL DISABILITY; LEARNING DISABILITY; Sexuality; Sexuality Studies; Sexuality and reproduction; gender and sexuality